Reading Awa Thiam's La parole aux Négresses through the lens of Feminisms and English Language Hegemony - Mianda, Gertrude (Atlantis, 2014)
In this paper, I argue that Awa Thiam’s pioneering analysis of women’s oppression that identified the interlocking systems of race, class, and sex has been ignored in mainstream Western feminism. As a result, African women, as producers of knowledge in feminism, have been seriously overlooked.